Antigen Extraction and B Cell Activation Enable Identification of Rare Membrane Antigen Specific Human B Cells - Zimmermann, Maria; Rose, Natalie; Lindner, John M.; Kim, Hyein; Gonçalves, Ana Rita; Callegari, Ilaria; Syedbasha, Mohammedyaseen; Kaufmann, Lukas; Egli, Adrian; Lindberg, Raija L. P.; Kappos, Ludwig; Traggiai, Elisabetta; et al. (Frontiers in Immunology, 2019)
Determining antigen specificity is vital for understanding B cell biology and for producing human monoclonal antibodies. We describe here a powerful method for identifying B cells that recognize membrane antigens expressed on cells. The technique depends on two characteristics of the interaction between a B cell and an antigen-expressing cell: antigen-receptor-mediated extraction of antigen from the membrane of the target cell, and B cell activation. We developed the method using influenza hemagglutinin as a model viral membrane antigen, and tested it using acetylcholine receptor (AChR) as a model membrane autoantigen. The technique involves co-culturing B cells with adherent, bioorthogonally labeled cells expressing GFP-tagged antigen, and sorting GFP-capturing, newly activated B cells. Hemagglutinin-specific B cells isolated this way from vaccinated human donors expressed elevated CD20, CD27, CD71, and CD11c, and reduced CD21, and their secreted antibodies blocked hemagglutination and neutralized viral infection. Antibodies cloned from AChR-capturing B cells derived from patients with myasthenia gravis bound specifically to the receptor on cell membrane. The approach is sensitive enough to detect antigen-specific B cells at steady state, and can be adapted for any membrane antigen.